"A Progressive Conservative": The Roles of George Perkins and Frank Munsey in the Progressive Party Campaign of 1912 - Cole, Marena. (2017)
Abstract: The election of 1912 was a contest between four parties. Among them was the Progressive Party, a movement begun by former president Theodore Roosevelt. George Perkins and Frank Munsey, two wealthy businessmen with interests in business policy and reform, provided the bulk of the Progressive Party's funding and proved crucial to its operations. This stirred up considerable controversy, particularly amongst the party's radical wing. One Progressive, Amos Pinchot, would later say that the two corrupted and destroyed the movement. While Pinchot's charge is too severe, particularly given the support Perkins and Munsey had from Roosevelt, the two did push the Progressive Party to adopt a softer program on antitrust regulation and enforcement of the Sherman Antitrust Act. The Progressive Party's official position on antitrust and the Sherman Act, as shaped by Munsey and Perkins, would cause internal ideological schisms within the party that would ultimately contribute to the party's dissolution.; Thesis (M.A.)--Tufts University, 2017.; Submitted to the Dept. of History.; Advisor: Reed Ueda.; Committee: David Ekbladh, and Patrick Maney.; Keyword: American history.